Quercetin Exerts Anticonvulsant Effect through Mitigation of Neuroinflammatory Response in Pentylenetetrazole-induced Seizure in Mice (Nigerian Journal of Physiological Sciences, 2023)
Epilepsy is a chronic disease of the brain characterized by seizures. The currently available anticonvulsants only treat symptoms with serious adverse drug reactions. Therefore, there is need for new therapeutic intervention that will prevent epileptogenesis with greater therapeutic success. Quercetin (QT) is a flavonoid with known neuroprotective and anti-inflammatory properties. The study aimed to investigate its effects against pentylenetetrazole (PTZ)-induced seizures. Animals were divided into four groups (n = 10). Group 1(control) only received vehicle (10 mL/kg), group 2 received vehicle, groups 3 and 4 received QT 12.5 mg/kg and 25 mg/kg respectively. Sixty minutes after treatments, animals in groups 2 to 4 were injected with sub-convulsive dose of pentylenetetrazole (35 mg/kg, i.p.) on every alternate day (48±2h) for 21 days. The mice were observed for 30 minutes after each PTZ injection for seizure activity. Brain samples were collected for biochemical assays. Administration of PTZ caused significant increase in the intensity of seizures, neuronal degeneration and level of proinflammatory cytokines in animals compared to control. These behavioural alterations were attenuated significantly by QT (12.5 and 25 mg/kg). The PTZ-induced increase in IL-12, TNF-α and IFN-ɣ were significantly reduced by pre-treatment with the QT (12.5 and 25 mg/kg, p.o). Quercetin also reduced neuronal loss compared to control. Quercetin attenuates seizures in kindled mice and reduces neuroinflammation and neurodegeneration. This neuroprotective effect may be attributed to its ability to inhibit inflammatory mediators in the brain